دور الإعلان عبر الإنترنت في مرحلة جمع المعلومات لمستهلكي الهاتف النقّال في السّاحل السّوري (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2017)
مع التطوّر الكبير في تكنولوجيا المعلومات والاتصالات، وانتشار الإنترنت بشكل كبير في مختلف أنحاء العالم، اتجهت منظمات الأعمال إلى استخدامه في الترويج لأعمالها ومنتجاتها. وكان الإعلان عبر الإنترنت أحد أهم عناصر الترويج الإلكترونية التي استخدمتها هذه المنظّمات؛ لما يقدمه من مزايا وفوائد وخاصة قدرته على توفير كم هائل من المعلومات التي يحتاجها المستهلكون ويبحثون عنها. فقد أصبح الإعلان عبر الإنترنت وخاصة في سورية وسيلة هامة جداً يلجأ اليها المستهلك من أجل الحصول على المعلومات التي يرغب بها عن المنتجات التي تعلن عنها هذه المنظّمات. يهدف هذا البحث إلى معرفة الدور الذي يلعبه الإعلان عبر الإنترنت في مرحلة جمع المعلومات المتعلّقة بعملية الشراء لدى المستهلكين في الساحل السوري. من خلال دراسة مسحية لعينة من مستهلكي الهاتف النقال في الساحل السوري تم فيها توزيع 185 استبانة. ومن النتائج التي توصلت إليها البحث أنّه لا تتوافر سرعات عالية للإنترنت تساعد المستهلك في مشاهدة الإعلان عبر الإنترنت بشكل مستمر. بالإضافة إلى أنّ الإعلان عبر الإنترنت يمكّن المستهلك من الحصول على معلومات كثيرة عن المنتج الذي يبحث عنه، كخصائص هذا المنتج، وأماكن تواجده، وأسعاره، كما أنّه يمكّن المستهلك من المقارنة بين الماركات المختلفة. ويوصي البحث بالعمل على تحسين شبكة الاتصال بالإنترنت، وزيادة سرعته؛ كي يتمكن المستهلك من مشاهدة الإعلان والحصول على المعلومات. بالإضافة إلى العمل على تصميم الإعلان عبر الإنترنت بطريقة تجذب المستهلك وتجعله يشاهد هذا الإعلان.With the large development of connection and information technology and spreading the internet in large way all over the world. Business organizations turned the using it in promotion for businesses and products. So the online advertising was one of the important factors for electronic promotion, which these organization used them for what it produced from characteristics and advantages and specially its ability for saving huge amount of information, which consumers need and search for. So the online advertising became and specially in Syrian important device. Which consumer use for getting on the information which he wishes. About the products that advertise about by these organizations. this research aims to knowing the role which the online advertising plays in the stage of collecting information that correlated in purchase process for consumers of mobile phone in the Syrian coast. through survey study group of consumers for the mobile phone in the Syrian cost in which 185 questioner where distributed. And from the results which the researcher came to that high fast is not available in the internet, which can help the consumer in watching the online advertising continuously. in addition to that online advertising enable the consumer from getting a lot of information about the product, which he search about as qualities of this product, its places and its prices. Also it enable consumer from comparing between different brands. The research advises by working on developing the internet and increasing its fast. So that the consumer can watch the internet and get the information in addition to working designing the online advertising in a way which a attracts the consumer and makes him watch this advertising.